EVALUATION OF ANTIOXIDANT EFFECT OF ALCOHOLIC ROOTS EXTRACT OF EUPHORBIA HIRTA LINN. – IN VITRO - WADHWA, RASHMI; GUPTA, PANKAJ (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The main objective of the present study was to undergo an investigation on free radical scavenging activity of the roots of Euphorbia hirta Linn. and was compared with a standard antioxidant compound like ascorbic acid. Methods: Euphorbia hirta roots extract was tested for total flavonoid content, total phenolic content, and in vitro antioxidant activity by 1, 1-diphenyl- 2-picrylhydrazyl (DPPH) free radical scavenging assay (DPPH) assay, superoxide anion radical scavenging assay, and nitric oxide scavenging assay. Results: The alcoholic roots extract of E. hirta was screened for free radical scavenging and antioxidant activities using three different methods. It was found that percentage inhibition of the extract was concentration-dependent. Total phenolic content and total flavonoid content were found to be 265.72±1.3 and 45.67±1.14, respectively. The alcoholic extract of E. hirta produced a dose-dependent inhibition of superoxide radicals ranging from 40.14±0.14 to 70.93±0.10. The mean IC50 values for DPPH radical by root extract of E. hirta and ascorbic acid were found to be 18.12 μg/ml and 13.17 μg/ ml, respectively. The alcoholic extract of E. hirta produced dose-dependent inhibition of nitric oxide radicals scavenging effect ranging from 17.05±0.18 to 51.08±0.30. The alcoholic extract of E. hirta and ascorbic acid shows mean IC50 values for superoxide radical as 23.64 μg/ml and 14.36 μg/ml, respectively. Conclusions: The present study showed that E. hirta possesses a considerable amount of both phenolic and flavonoid content. The alcoholic root extract also shows good antioxidant potential. The results of the present study also encourage for further in vivo studies and isolation and characterization of active compounds.